2019
DOI: 10.7812/tpp/18-041
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol in Anxiety and Sleep: A Large Case Series

Abstract: 1829 patients underwent radical prostatectomy with pelvic lymph node dissection (RP+PLND) (241 high-risk, 943 intermediate-risk, 645 low-risk). Positive margin rates were 17.8%, 14.8%, and 11.9% in the high, intermediate-and lowrisk groups. Five-year overall survival was 92.5% in lymph node-positive patients and 94.9% in lymph node-negative patients (p = 0.8). Age, prebiopsy prostatespecific antigen, and clinical stage were associated with positive surgical margins in patients with lymph node metastasis (LNM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
201
2
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(227 citation statements)
references
References 18 publications
5
201
2
19
Order By: Relevance
“…Numerous preclinical trials 9,10 and neuro-imaging studies 8 have demonstrated the anxiolytic effects of CBD. A recently published case-series in psychiatric patients found a benefit of CBD for anxiety and sleep, 16 which is in agreement with the above findings.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…Numerous preclinical trials 9,10 and neuro-imaging studies 8 have demonstrated the anxiolytic effects of CBD. A recently published case-series in psychiatric patients found a benefit of CBD for anxiety and sleep, 16 which is in agreement with the above findings.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…In a 10-year-old patient, 5 months of treatment with CBD oil (25 mg) and liquid CBD (6-12 mg) in a sublingual spray as needed was associated with less anxiety and better sleep quality, with no adverse effects (Shannon & Opila-Lehman, 2016). These results were replicated for anxiety in a recently published chart review of 72 adult patients with insomnia and anxiety (Shannon et al, 2019). Most patients in this group were given 25 mg CBD/day, while a few patients were given 50 or 75 mg/day, and one patient with schizoaffective disorder and trauma was given up to 175 mg/day.…”
Section: Other Disordersmentioning
confidence: 75%
“…One case report on the use of CBD by two patients with bipolar disorder showed limited to no improvement with doses of 600-1200 mg for bipolar mania in one of the patients (Shannon et al, 2019). The second patient (OCEBM, 2019).…”
Section: Other Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A trial of oral CBD oil (25 mg) resulted in a decrease in this patient's anxiety, and improvement in the quality and quantity of her sleep. A more substantial retrospective case series of 72 adults given CBD for anxiety and sleep complaints at a psychiatric clinic (as an adjunct to usual treatment) assessed patient data monthly over 12 weeks [70]. Anxiety scores on the Hamilton Anxiety rating Scale (HAMA) decreased within the first month in 79% of the sample and remained low during the study duration.…”
Section: Insomniamentioning
confidence: 99%